TOWARDS SUCCESSFUL ORGANIZATIONAL CHANGE MANAGEMENT - NEW PROCESS MODEL IDENTIFICATION - Vrcelj, Nikolina (Journal of process management and new technologies, 2023)
The ever-evolving corporate landscape, catalyzed by the COVID-19 pandemic and rapid advancements in information technologies, has given rise to a new organizational philosophy. As novel sectors emerge and new forms of work and business processes unfold, change becomes a necessity integrated into companies' survival strategies. The dynamic, diverse, and discontinuous nature of the contemporary business environment demands a deeper understanding of organizational changes. Despite the prevalence of change, a significant number of initiated change programs fail, emphasizing the need for effective change management. While numerous change management theories exist, empirical validation and practical testing are often lacking, creating a gap between theory and application. This paper presents a critical exploration of prominent process models of organizational change, aiming to identify a unified diagnostic process model that addresses existing shortcomings and leverages the strengths of these models. The research identifies ten common phases in various process models, leading to the formulation of a 10F process model of organizational change. This model encompasses crucial stages such as problem diagnosis, creating a sense of urgency, establishing leadership roles, vision creation, planning, communication, implementation, short-term results, stabilization, and monitoring. The 10F model offers a comprehensive framework for understanding and managing diverse organizational changes. This research contributes to bridging the gap between theory and practice, providing valuable insights for managers, researchers, and practitioners engaged in organizational change initiatives.